Lower body mass index is an independent predictor of mortality in older patients with acute respiratory distress syndrome - Jia-Jun Wu; Wei-Fan Ou; Yu-Yi Yu; Chieh-Liang Wu; Tsung-Ying Yang; Ming-Cheng Chan (Heliyon, 2024)
Background: Acute respiratory distress syndrome (ARDS) is associated with high mortality. The impacts of body mass index (BMI) on the morality of older patients with ARDS remain unclear. Methods: This is a single-center cohort study which was conducted at Taichung Veterans General Hospital, Taiwan. Adult patients admitted to the ICU needing mechanical ventilation with ARDS were included for analysis. We compared the data of older patients (age ≥65 years) with those of younger patients (Age <65 years). The factors associated with in-hospital mortality of older patients were investigated. Results: This study included a total of 728 (mean age: 66 years; men: 63%) patients, and 425 (58.4%) of them aged ≥65 years. Older patients exhibited lower body mass index (BMI) (23.8 vs 25.2), higher Acute Physiology and Chronic Health Evaluation (APACHE) II scores (28.9 vs 26.3), higher Charlson Comorbidity Index (CCI) (4.0 vs 3.4), and lower Sequential Organ Failure Assessment (SOFA) scores (10.0 vs 11.1) than younger patients. Furthermore, older patients had mortality rates similar to younger patients (40.5% vs 42.9%, P = 0.542), but had longer length of stay in the ICU (17.6 vs 15.6 days, P = 0.047). For older patients, BMI <18.5 (odds ratio [OR], 2.78; 95% confidence interval [CI], 1.45–5.34), high SOFA score (OR, 1.20; 95% CI, 1.12–1.28), and moderate (OR, 1.95; 95% CI 1.20–3.14) or severe ARDS (OR, 2.30; 95% CI 1.26–4.22) were independent risk factors for mortality. Conclusions: In this cohort, critical ill older patients with ARDS had lower BMI, more comorbidities, and higher APACHE II scores than younger patients. Mortality rate was similar between older and younger patients. Low BMI, high SOFA score, and moderate or severe ARDS were independently associated with mortality in older patients with ARDS.